Burnerverse - Graham St John; Botond Vitos (Journal of Festive Studies)
Otherwise known as Black Rock City, Burning Man is a remote fire-arts gathering in Nevada’s Black Rock Desert that has catalyzed a global movement. An ephemeral community flowering in a desert, Burning Man is also a cultural proliferation of events that model and mutate the Black Rock City prototype worldwide. Cyclical and augmentative, replicable and mutable, Burning Man has evolved from a small cultural event into a transformative event culture. This article presents research from a longitudinal project addressing the ostensible “transformational” quality of Burning Man and its cultural archipelago of events. Informed by the complex spatialization inherent to Michel Foucault’s “heterotopia,” it navigates the “hyper-liminal” dynamics of two “regional events” and their organization models: Midburn (Israel) and the Borderland (Nordic). The heterotopic process promotes insight on disparate practices within cultural “other spaces”: here, Black Rock City and the events, or “burns,” it has spawned. Tracking the storied career of the Burning Man ethos known as the “10 Principles” as this is transmitted via “ritualesque” and “carnivalesque” performances, the article sheds light on ways local circumstances refract, filter, and mutate Burner culture, from carbon-copied transplants to innovative independent solutions. In other words, the article explores how this transformative cultural movement undergoes transformation, specifically addressing how, as they mimic and mutate the prototype and its principles, regional burns are contexts for authorization and subversion. This multi-sited navigation of burn event spaces that are imitative and imaginative, and of a principled culture that is mirrored and contested, offers a unique contribution to the study of “transfestive” event cultures.